Synchrony in Human-Bonobo Dialog - Koutsombogera, Maria; Vogel, Carl (IEEE, 2020)
Past research has suggested that bonobos have demonstrated capabilities of successful linguistic interaction with humans. A transcript of interactions linked to such claims is analyzed using methods that have been deployed to assess mutual understanding in human communication. Evidence of dialog plan maintenance on the part of the bonobo is visible, but not of understanding of the human dialog partners (nor vice versa,mostly).
11th IEEE International Conference on Cognitive Infocommunications
Keywords: Data Analysis